2021
DOI: 10.1007/s00540-021-02971-3
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human thrombomodulin for pneumonia-induced severe ARDS complicated by DIC in children: a preliminary study

Abstract: Purpose Recombinant human soluble thrombomodulin (rTM) has been used to treat disseminated intravascular coagulation (DIC). Recent studies have shown the efficacy of rTM through its anti-inflammatory effects for treatment of adults with acute respiratory distress syndrome (ARDS). However, the safety and efficacy of rTM in children with severe ARDS complicated by DIC have not been reported. In this preliminary study, we reported the feasibility of using rTM for the treatment of pneumonia-induced severe ARDS com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In addition to the effect of ROS on cell–cell interactions, ROS are also involved in altering coagulation and fibrinolysis, contributing to ARDS ( Figure 5 ) [ 159 , 160 , 161 ]. However, further research is necessary to understand the underlying principles in detail [ 162 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the effect of ROS on cell–cell interactions, ROS are also involved in altering coagulation and fibrinolysis, contributing to ARDS ( Figure 5 ) [ 159 , 160 , 161 ]. However, further research is necessary to understand the underlying principles in detail [ 162 ].…”
Section: Methodsmentioning
confidence: 99%
“…TM may have a physiopathologic role in thromboembolic disorders, ischemia-reperfusion syndromes, sepsis, malignant hypertension, and ARDS [108][109][110]. A single study reported that administration of recombinant TM significantly reduced acute GVHD (a-GVHD) and ameliorated OS after allogeneic hematopoietic stem cell transplantation [111].…”
Section: Thrombomodulinmentioning
confidence: 99%
“…A single study reported that administration of recombinant TM significantly reduced acute GVHD (a-GVHD) and ameliorated OS after allogeneic hematopoietic stem cell transplantation [111]. TM has been found clinically helpful as a therapy for DIC in children [112][113][114] and ARDS [108]. ure 8).…”
Section: Thrombomodulinmentioning
confidence: 99%
See 1 more Smart Citation
“…A clinical trial of this soluble human thrombomodulin was conducted, and a manufacturing and marketing approval application was submitted for the treatment of DIC in 2006, following which the drug was approved in January 2008 [ 17 , 18 ]. Studies have reported that rTM exerts a therapeutic effect on DIC caused by infectious diseases, malignant tumors, trauma, and gynecological diseases [ 19 , 20 , 21 ]. The mechanism underlying the action of rTM involves promoting the activation of protein C by thrombin, and the generated activated protein C decomposes the coagulation-promoting factors Va and VIIIa using protein S as a coagulation factor to generate thrombin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%